Poverty, Vulnerability and Family Size: Evidence from the Philippines - Aniceto C. Orbeta (Asian Development Bank Institute (ADBI), 2005)
The population and poverty nexus is not new but remains an important development issue for many countries. Recent research has added the crucial dimension of vulnerability to poverty to the debate on the determinants of the welfare status of a population. But the issue of vulnerability has hardly been dealt with using Philippine data. This paper, therefore, draws together recent results using household survey data regarding the impact of family size on various aspects of family welfare in the Philippines. In particular, it shows results of cross-tabulation and multivariate analyses of the role of family size on such areas as poverty incidence, vulnerability to poverty, as well as the underlying mechanism of savings, labor supply and earnings of parents and human capital investments. There are several conclusions that can be made from the evidence presented. One, there is a clear negative impact, on average, from additional children on household welfare. Two, and more importantly, these negative impacts are regressive, i.e. the negative impacts on poorer households are larger. Three, the associations between larger family size, poverty incidence and vulnerability to poverty are strong and enduring. These results have important implications for efforts at poverty reduction—the centerpiece program of many Philippine administrations though without much success. Many attribute this lack of success to low and inconsistent growth rates. This paper adds large family size as an obvious, but not well-understood reason, not only for the low and inconsistent economic growth rates but also for direct debilitating effects on many aspects of household welfare. The results of this paper point to several implications for policy. First, a strong population program must accompany poverty alleviation efforts. In the short run, it may be in the form of providing family planning services for those who need them. In the long run, it may include advocacy for smaller family size. The negative impact of large family size on household savings pointed out in this study has an impact both macro-economically and on households. Larger family size reduces household savings, lowering the already low national savings. This hampers investment, particularly in an environment like the Philippines where foreign direct investment is not high. Having additional children also prevents more school-age children from attending school and leads more to enter child labor. From the perspective of development measured in terms of capabilities, helping families achieve their desired family size directly increases their well being, all other things being constant. Second, there is a limit to what employment generation programs, even when they can be implemented, can do for large families. Additional children, as the results of this study show, hinder mothers from taking on employment, particularly, paid employment. Third, there is a need to stop the implied intergenerational transmission of poverty indicated by the negative impact of the number of children on school attendance. There is perhaps room for education subsidies directed at large families. Fourth, targeting poor households also means targeting large households and vice-versa. In addition, considering the regressiveness of the impact of additional children, there will be larger impacts from targeting poorer or larger households.
hdl:11540/4174
Keywords: 330